Development of a multi-step screening procedure for redox active molecules in organic radical polymer anodes and as redox flow anolytes - Achazi, Andreas J.; Fataj, Xhesilda; Rohland, Philip; Hager, Martin D.; Schubert, Ulrich S.; Mollenhauer, Doreen; Justus Liebig University Giessen (My University, 2024)
Benzo[d]-X-zolyl-pyridinyl (X=O, S, NH) radicals represent a promising class of redox-active molecules for organic batteries. We present a multistep screening procedure to identify the most promising radical candidates. Experimental investigations and highly correlated wave function-based calculations are performed to determine benchmark redox potentials. Based on these, the accuracies of different methods (semi-empirical, density functional theory, wave function-based), solvent models, dispersion corrections, and basis sets are evaluated. The developed screening procedure consists of three steps: First, a conformer search is performed with CREST. The molecules are selected based on the redox potentials calculated using GFN2-xTB. Second, HOMO energies calculated with reparametrized B3LYP-D3(BJ) and the def2-SVP basis set are used as selection criteria. The final molecules are selected based on the redox potentials calculated from Gibbs energies using BP86-D3(BJ)/def2-TZVP. With this multistep screening approach, promising molecules can be suggested for synthesis, and structure–property relationships can be derived.
Keywords: ddc:540